Closing the loop of textile: Circular building renovation with novel recycled insulations from wasted clothes - Andrea Augello; Olga Beatrice Carcassi; Francesco Pittau; Laura Elisabetta Malighetti; Enrico De Angelis (Acta Polytechnica CTU Proceedings)
The implementation of new energy policies and standards for NZEB is expected to lead to a significant reduction of GHG emissions from building use in Europe in the next decades. On the other side, the growing pressure on insulation materials risks to significantly contribute to the exhaustion of the remaining carbon budget due to the high carbon intensity of conventional insulation for material processing. Consequently, storing carbon in construction products and promoting circular economies able to generate up-cycling processes from industrial or post-consumption waste are the key strategies to promote an effective transition toward a carbon-neutral society. Fashion & clothing is one of the manufacturing sectors which mostly contributes to waste generation and fossil GHG emission. This paper presents the main outcomes achieved from RECYdress project, which focuses on the valorisation of wasted textile collected by municipal districts to develop novel thermal insulations for building applications. Three alternative conceptual manufacturing processes were defined at lab scale based on different treatment of textile fibres, with produced specimens tested for thermal characterization. Finally, the LCA results of an ETICS application for façade renovation were compared considering as functional unit 1m2 of façade with similar thermal resistance.